The Difficult Neck in Facelifting - Roy, Sudeep; Buckingham, Edward (Facial Plastic Surgery, 2017)
As the popularity and acceptance of facial and cervical rejuvenation procedures grows, surgeons are increasingly encountering patients with less favorable anatomical characteristics for rhytidectomy. These patients will typically display an obtuse cervicomental angle, underprojected chin, excess cervical adiposity, and platysmal banding, in addition to ptotic submandibular glands, tenacious jowls, and prejowl volume deficits. Recognition of these problems and the correct application of available techniques to address the difficult neck in facelifting are critical in maximizing success.
Keywords: facelift; difficult neck; SMAS; platysmaplasty